EFFECTS OF ABUSE ON ADOLESCENTS' MENTAL, SOCIAL, AND PHYSICAL HEALTH (The Research of Medical Science Review, 2024)
This paper explores the multifaceted impact of abuse on adolescents, focusing on their mental, social, and physical well-being. Abuse during these formative years can lead to significant psychological issues, including anxiety, depression, and low self-esteem, which hinder emotional development and coping mechanisms. Socially, adolescents may experience isolation, difficulties in forming healthy relationships, and a heightened risk of engaging in harmful behaviors. Physically, the effects of abuse can manifest as chronic health problems, substance abuse, and risky behaviors that jeopardize overall health. This study emphasizes the need for comprehensive support systems to address the complex needs of abused adolescents and promote recovery and resilience.